EXPLORING ETHNOMATHEMATICS IN THE TRADITIONAL GAME NAMED ENGKLEK - Afghohani, Afif; Cahyaningrum, Fatwiyati Sholikhah; Astutiningtyas, Erika Laras (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2024)
This study examines some mathematical objects can be learned from the traditional engklek game activities in Kampung Dolanan Sidowayah. Specifically, the purpose of this study is to find out the mathematical elements that exist in the traditional game engklek, Using a descriptive approach, the subjects of this study were Budayawan, Kampung Dolanan Sidowayah Manager, and children around Kampung Dolanan Sidowayah. Data was studied using techniques following the Spradley model include domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The results showed that the traditional game engklek contains mathematical elements, namely flat planes, semicircular elements, cube webs, congruence, geometric transformations, angles, relationships between lines, line segments, flat plane area, sets, odds, permutations, numerations, distances, and implications. Having this traditional game, students might develop perspective of mathematics in their culture.